Türkiye'deki Fen Bilimleri Öğretmenliği Programlarının Genel Durumlarının ve Atama Sayılarının İncelenmesi. - TAFLI, Tuğba (Selcuk University Social Sciences Institute / Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi, 2021)
The aim of this study is to determine the general situation of the Science Education Programs of all universities in Turkey about the last 5 years. Document analysis method, the first placement and additional placement tables announced by OSYM for the years of 2016-2020, was used in the study and the results of all science teaching programs data were organized according to the content analysis tecnique. In this context, regarding the departments of science education, biology education, physics education and chemistry education were organized separately by years about in which universites has these programs, the number of their general quotas, the number of students placed in these programs and the occupancy rates on each universities. The number of teacher appointments made by the Ministry of National Education (MEB) for science teachers was also examined by limiting it to the same years. As a result of the analysis, it has been observed that the general quota of all science education programs has decreased considerably in the last 5 years. The occupancy rates of the students who were placed in the relevant programs in 2017 and 2018 decreased with the success ranking condition that was implemented after 2017, which was almost 100% in 2016 in all branches of science education. Due to the reduced occupancy of the programs and the quotas, the results showed that the occupancy rates was started to increase in 2019 and the occupancy rate reached full capacity again as of 2020.